Unsupervised digital movie restoration with spatial models of color - Rizzi, Alessandro; Berolo, Anna Jerry; Bonanomi, Cristian; Gadia, Davide (Multimedia tools and applications, 2016)
In this paper, we present an efficient approach to digital color restoration, based on the idea of recovering the appearance of color rather than the original color signal, since, in most of the cases, for old films the original reference is missing, and new films or digital coding can be subject to severe gamut transformations. This approach is based on the application of algorithms inspired by the capabilities of the Human Vision System of automatically adjust to the variation of color and lightness in the scene. The proposed method allows more unsupervised restoration. We present an overview of the approach, characteristics of this family of algorithms, and restoration examples.